Utilization of Coffee Commodity Agricultural Waste Through Partnership Towards Sustainable Production and Consumption - Herlyna Novasari Siahaan; Hendris Syah Putra; M. Fariz Afif Hasibuan (Jurnal Biologi Tropis, 2023)
One of the SDGs for the process of coffee production and consumption through partnerships is SDGs 12 and 17. SDGs 12 relates to Responsible consumption and production and SDGs 17 relates to partnerships for the Goals. Efficient management of waste management is an important target for achieving SDGS 12 goals to move towards a more sustainable consumption pattern by 2030. Coffee production is increasing every year accompanied by an increase in coffee consumption and drinking trends around the world. This research was conducted at Satya Terra Bhinneka University by holding a Focus Group Discussion (FGD) by inviting stakeholders consisting from farmers, government, business world and academics. on July 20 2023. The data collection method was carried out using the PRA (Participatory Rural Appraisal) method and analyzed in a descriptive. The research results show that coffee farmers in North Sumatra Province are spread across several districts which produced Arabica and Robusta while the original coffee variety is “Sigarar Utang”. Coffee farmer institutions in North Sumatra are in the form of farmer groups, farmer group associations and farmer cooperatives to managing plantations by implementing agricultural corporations. The use of coffee waste is making compost and liquid organic fertilizer. Coffee waste is also used as a Cascara drink and making coffee ashtrays.